ANALISIS YURIDIS TERHADAP PENGATURAN TINDAK PIDANA KORUPSI SETELAH DIKELUARKANNYA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 25/PUU-XIV/2016 - Rajagukguk, Iin Octavia; Jamba, Padrisan (LPPM Universitas Putera Batam, 2019)
There is an increase in corruption level in Indonesia, both inathe total numberaofacases andainathe total amount of financial losses suffered by the state. There are even more systematic corruption which present in all aspect of social life.The main problem formulation would be focusing on the consideration upon the decision of the panel of judges ofatheaConstitutionalaCourt in its decision Numbera25/PUU-XIV/2016aand its legal implication towards law enforcement process andacorruption eradication.aThe objective of thisaresearch is, first, to understand the legal consideration of the panel of judges of constitutional court in the decision Number 25/PUUXIV/2016. As for the second objective, the researcher would like to be cognizant of the legal qualification related with the law enforcement andacorruptionaeradication process. In conducting the research, the researcher is using normative judicial research, with juridical approach as the method. This research is using qualitative method and in analytical-descriptive analysis. This research resulted in number of conclusions, per se, Constitutional Court decision Number 25/PUUXIV/2016 has created legal uncertainty related to the formulation of corruption; as corruption was material offense, whereof in the beginning was formal offense. Such circumstance obliges law enforcer to establish the ground on how much actual financial loss the state has suffered, not on potential financial loss. There is different, legally unrelated perspective in defining “could” as in “could inflict state financial loss or harm state economy” under criminal approach of Law on Corruption Eradication and under administrative approach of Law Number 30 Year 2004.